Kekuasaan di Sekolah: Tingkat Penggunaan Basis Kekuasaan Posisi (Position Power) - Lanin, Dasman (Jurnal Demokrasi, 2002)
The purposes of this article are to describe the use of power, especially position power in a school. The position power constrains: coercive power, connection power, reward power, and legitimate power. Using this power by principal will cause response from teacher, either rejection or acceptation. One research study showed that only one of four position powers was used by high level (legitimate power) and others were used by low level. Â  Key Words: Penggunaan Kekuasaan (The use of power)